2019
DOI: 10.2116/analsci.19p272
|View full text |Cite
|
Sign up to set email alerts
|

Resonance-enhanced Multiphoton Ionization Time-of-Flight Mass Spectrometry for Evaluating Emulsion Inversion via Temperature Change

Abstract: This study used resonance-enhanced multiphoton ionization time-of-flight mass spectrometry (REMPI-TOFMS) to evaluate the phase inversion that is driven via temperature change. A change in temperature prompts phase inversion in an oil-in-water (O/W) emulsion that uses a nonionic surfactant as an emulsifier. In this study, an O/W emulsion was prepared containing Triton X-100 as an emulsifier. To promote emulsion inversion, we heated only the outlet of a capillary column that was used for sample introduction duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…[19][20][21][22] Recently, we applied REMPI-TOFMS to the analysis of an emulsion without pretreatment. [23][24][25] In this technique, an emulsion is flowed through a capillary column and is continuously introduced into TOFMS. Then a series of mass spectra are recorded, the peak areas of a target species are extracted from the series of mass spectra, and finally a time profile of the peak areas can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Recently, we applied REMPI-TOFMS to the analysis of an emulsion without pretreatment. [23][24][25] In this technique, an emulsion is flowed through a capillary column and is continuously introduced into TOFMS. Then a series of mass spectra are recorded, the peak areas of a target species are extracted from the series of mass spectra, and finally a time profile of the peak areas can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Resonance-enhanced multiphoton ionization time-of-flight mass spectrometry (REMPI-TOFMS) using ultraviolet (UV) pulses for ionization is a selective analytical method. 13 17 Namely, compounds with absorption against the laser wavelength that is applied, mainly aromatic compounds, can be sensitively and selectively detected. Until now, Zimmermann et al have reported applications in evaluating volatile flavor compounds during coffee roasting.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we demonstrated the evaluation of an emulsion where phase inversion had occurred via a temperature change. 13 In that report, a capillary column was used for sample introduction, and when the temperature of the column was low (40 °C), several positive spikes were detected. This indicated that the emulsion was surely an O/W emulsion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have reported a method for the direct analysis of an emulsion without pretreatment using resonance-enhanced multiphoton ionization time-of-flight mass spectrometry (REMPI-TOFMS). REMPI has superior spectroscopic selectivity and produces fewer contaminants, and TOFMS is easy to clean because of the simple structure, even when there is contamination. These advantages make REMPI-TOFMS suitable for the measurement of an emulsion where the concentrations of the constituents are inherently high.…”
Section: Introductionmentioning
confidence: 99%